Community‐based healthcare costs for children born low birthweight, preterm and/or small for gestational age: data from the Longitudinal Study of Australian Children. Issue 2 (5th March 2013) - Westrupp, E. M.; Lucas, N.; Mensah, F. K.; Gold, L.; Wake, M.; Nicholson, J. M
Abstract Aim Children born low birthweight, preterm and/or small for gestational age (SGA) sustain substantially increased costs for hospital‐based health care and additional educational support in the first few years of life. This is the first study internationally to investigate costs beyond hospital care, to community‐based health care and prescription medicines across early and middle childhood with actual cost data, and to examine these costs according to the severity of perinatal risk. Method In the prospective Longitudinal Study of Australian Children, we followed two cohorts of children from age of 0 to 5 years (no increased perinatal risk, n = 3973; mild risk, n = 442; and moderate‐to‐high risk, n = 297), and from age of 4 to 9 years (no increased perinatal risk, n = 3629; mild risk, n = 465; and moderate‐to‐high risk, n = 361). Children were defined as mild risk if born 32–36 weeks, with birthweight 1500–2499 g, and/or SGA (<5–9th percentile), and moderate‐to‐high risk if born <32 weeks, birthweight <1500 g and/or extremely SGA (<5th percentile). Federal government expenditure (2011 AUD) on healthcare attendances and prescription medication from birth to 9 years were calculated via data linkage to the Australian Medicare records. Results Mean costs per child were A362 higher (95% CI 156; 568) from 0 to 5 years and A306 higher (95% CI 137; 475) from 4 to 9 years, for children with any compared with no increased perinatal risk (P < 0.001). At the population level, an additional A32m was spent per year for children 0–9 years with any relative to no increased perinatal risk. Conclusions Perinatal risk is a major public health issue conferring considerable additional expense to community‐based health care, most marked in the first year of life but persisting up to at least 10 years. Even without additionally considering burden, these findings add to the urgency of identifying effective mechanisms to reduce perinatal risk across its full spectrum.